Physical activity and associated factors among Indonesian pregnant women: a mixed-method study - Feva Tridiyawati; Dg Marshitah Pg Baharuddin; Nicholas Pang (Intelektual Pustaka Media Utama, 2026)
Exercise is recommended for pregnant women, but many are sedentary. Studies on barriers to physical activity and exercise among pregnant women in West Java Province, Indonesia, are scarce. This study aims to identify and explore the underlying factors associated with physical activity during pregnancy in West Java, Indonesia. This study was conducted using a mixed-methods strategy that integrates quantitative and qualitative data. The study surveyed pregnant women in West Java, Indonesia, from January to March 2023. The study involved 18-year-olds, married women, and fluent Bahasa participants. It used a questionnaire to assess physical pregnancy activity intention, and analyzed data using descriptive, correlation withp<0.025 included in linear regression analysis. While in a qualitative study used semi-structure interview. A study of 200 pregnant women found that age negatively correlated with total metabolic equivalent of task (MET), while gestational age, education level, body mass index (BMI), and pregnancy complications positively impacted it. Pregnancy symptoms, limited time, and low social support were identified as themes impacting adhering to physical activity recommendations. The study reveals that factors such as age, gestational age, education level, BMI, and pregnancy complications significantly influence total MET in pregnant women, suggesting the need for personalized interventions.